Workshop Bedah Buku “Kajian Kebijakan Politik Internasional: Metode, Teori dan Kasus” di Universitas Panca Marga - Fitria, Nurul Jannah Lailatul; Puspitarini, Renny Candradewi (Jurnal Dharma Bhakti Ekuitas, 2023)
Community service activities are carried out for 2019 batch students of the Public Administration Study Program, Faculty of Social and Political Sciences, Panca Marga University. This activity is based on the results of observations on partners regarding the urgency of understanding international political policy studies. The method of implementing community service consists of seven stages summarized in pre-activity, during activities, and post-activity. Pre-activities carried out in-depth observations and coordination with competent resource persons as well as authors of International Political Policy Studies books. During the activity, partners were presented with material through power points and interactive communication during material delivery and question and answer sessions. After the activity, partners are still monitored by uploading videos on YouTube accounts and conducting evaluation questions to partners to find out partners' understanding of the workshop material. The advantages of the Book Review Workshop "International Political Policy Studies: Methods, Theories and Case Studies" is to pay attention to the needs of partners related to the lack of understanding of international political policy. So that students, especially students of the FISIP Public Administration Study Program who will or have taken international political policy courses, can analyze this material appropriately. Community service activities aim to provide understanding, knowledge, insight, and additional new perspectives to 2019 students of the FISIP Public Administration study program at Panca Marga University about the importance and urgency of understanding international political policy in terms of definition, scope, system, and others. Keywords: Explanation, International, Study, Policy; Political. Abstrak Kegiatan pengabdian masyarakat dilaksanakan pada mahasiswa angkatan 2019 Prodi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Panca Marga. Kegiatan ini didasari hasil observasi pada mitra terkait urgensi pemahaman kajian kebijakan politik internasional. Metode pelaksanaan pengabdian masyarakat terdiri dari tujuh tahap yang dirangkum pada pra-kegiatan, saat kegiatan, dan pasca kegiatan. Pra-kegiatan dilakukan observasi mendalam dan koordinasi dengan narasumber yang berkompeten sekaligus penulis buku Kajian Kebijakan Politik Internasional. Saat kegiatan, mitra dipaparkan materi melalui power point dan komunikasi interaktif saat penyampaian materi dan sesi tanya jawab. Pasca kegiatan, mitra tetap dipantau dengan melakukan unggahan video pada akun youtube dan mengadakan pertanyaan evaluasi pada mitra untuk mengetahui pemahaman mitra pada materi workshop. Keunggulan Workshop Bedah Buku “Kajian Kebijakan Politik Internasional: Metode, Teori dan Studi Kasus” adalah memperhatikan kebutuhan mitra terkait kurangnya pemahaman kebijakan politik internasional. Sehingga mahasiswa khususnya mahasiswa Prodi Administrasi Publik FISIP yang akan atau telah menempuh mata kuliah kebijakan politik internasional dapat menganalisis materi ini dengan tepat. Kegiatan pengabdian kepada masyarakat bertujuan memberikan pemahaman, ilmu, wawasan, dan tambahan sudut pandang baru kepada mahasiswa angkatan 2019 prodi Administrasi Publik FISIP di Universitas Panca Marga tentang pentingnya dan urgensi memahami kebijakan politik internasional dari segi definisi, ruang lingkup, sistem, dan lainnya. Kata kunci: Eksplanasi, Internasional, Kajian, Kebijakan, Politik.